Hubungan Praktik Pemberian Makan dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Plosoklaten Kabupaten Kediri - Khusnatul Mar'atik; Lailatul Muniroh (Media Gizi Kesmas, 2023)
Background: Stunting is a growth retardation as result of inadequate nutrition for a long time and recurrent infections during the first 1000 days of a child's life.  One of the direct factors causing stunting is inadequate food consumption for a long time. Food consumption in toddlers is still highly dependent on their parents, so that feeding practices greatly affect the toddlers' nutrition status. Objectives: The study aims to analyze the correlation between feeding practices with stunting in toddlers aged 6-60 months in the Puskesmas Plosoklaten, Kediri Regency. Methods: This study was an observational study with a cross sectional design. The number of samples in this study were 72 toddlers in the Puskesmas Plosoklaten, Kediri Regency. Data were collected by interviewing mothers and filling the Food Frequency Questionnaire (FFQ) to determine the type of food served and a 2x24 hour food recall form to obtain data of portion and frequency of food consumption. Then the collected data was analyzed using the Spearman's rho test. Results: The results of this study showed that there was a correlation between feeding practices based on the suitability of food portion sizes and the incidence of stunting (p=0.013). However, no correlation was found between feeding practices based on a dietary diversity and meal frequency with the incidence of stunting (p=0.178 and p=0.381). Conclusions: There were more stunted toddlers in mothers who gave < 3 types of food with appropriate portions. Puskesmas needs to provide information regarding adequate food portions according to the age, so that adequate consumption is achieved and the nutritional needs can be met.